Association Between Indoor Air Quality and Sick Building Syndrome Among Workers in Food Outlets in Selangor, Malaysia - Ismahani Isman, Nur Izzah; Jalaludin, Juliana; Suhaimi, Nur Faseeha; Fahimah Hashim; Abdul Rohim Tualeka (JURNAL KESEHATAN LINGKUNGAN, 2024)
Introduction: Indoor air pollution, causing health issues like Sick Building Syndrome (SBS), is the third largest global contributor to disability-adjusted life years, emphasizing the urgent need for improved indoor air quality. This study aimed to determine the association between Indoor Air Quality (IAQ) and SBS among workers at food outlets in Selangor, Malaysia. Methods: A cross-sectional study was carried out among 107 workers in mall, new and old food outlet. A set of standardized and validated version questionnaires of the Industry Code of Practice on Indoor Air Quality (ICOP IAQ) 2010 was distributed to obtain respondents’ sociodemographic information, symptoms present at the workplace, and psychosocial information. Results and Discussion: The study found significant differences in temperature (p = 0.004), air velocity (p = 0.037), ultrafine particles (p = 0.005), and carbon dioxide (CO2) concentrations (p = 0.006) in malls, new and old food outlets. Workers in old food outlets had the highest prevalence of SBS (66.7%), compared to those in new outlets (60.5%) and mall outlets (64.7%). Environmental characteristics, such as increased dust and particulate matter during renovation (OR = 6.17, 95% CI = 1.34-28.34), repair (OR = 2.43, 95% CI = 1.03-5.76), along with temperature variations (OR = 7.21, 95% CI = 2.52-20.66) significantly influencing SBS. Conclusion: SBS prevalence in food outlets is not significantly linked to IAQ parameters, but exposure to UFP and PM2.5 may contribute to its development. However, it is significantly associated with workplace renovations and repairs for interior design, as well as varying temperatures.